Children’s physical custody arrangements and mothers’ employment in 11 European countries - Salin, Milla; Hakovirta, Mia; Lindroos, Eija; Meyer, Daniel R. (Informa UK Limited, 2026)
As joint physical custody (JPC) of children after parental separation has become more prevalent across countries, we need to know more about its impacts. This study examines whether JPC is associated with mother's paid employment given that childcare responsibilities are redistributed more equally between parents compared to mothers with sole physical custody (SPC). We provide the first comparative analysis on the relationship between a child's physical custody arrangement type and mother's employment across 11 European countries. Data are from the 2021 European Union Statistics on Income and Living Conditions Survey (EU-SILC). Our sample includes 3,846 mothers. We employ descriptive statistics, binary logistic regression analysis and decomposition analysis. Results reveal an employment gap between mothers with JPC and SPC: mothers with JPC are more likely to be employed than mothers with SPC, even when controlling for individual-level confounding factors and country context. Moreover, results show that only around half the employment gap between JPC mothers and SPC mothers can be explained by differences in characteristics and country context. Thus, we argue that JPC is likely to have an independent role on mothers' employment, and JPC eases the constraints of mother's paid work opportunities.